Analysis of Personnel Training and Development Programmes in Lapetal Disminpersal to Improve Quality Navy Recruitment - Alex Sondra, William; Ferry Cahaya, Yohanes (Dinasti Publisher, 2025)
This study aims to analyse the personnel training and development programme at the Disminpersal Education and Training Institute (Lapetal) to improve the quality of recruitment of the Indonesian Navy (TNI AL). This research uses a qualitative approach with a descriptive analysis method to explore the challenges Lapetal is facing in achieving this goal. The analysis results show that Lapetal faces several significant challenges, mainly related to the educational level of personnel who have not met expectations and the gap between personnel competence and increasingly complex task demands. The less-than-optimal training and development programmes currently in place are contributing internal factors. To address these issues, this study recommends several strategies, including (1) the use of information technology to improve efficiency in the recruitment process and competency development, (2) increased cooperation with educational institutions to strengthen access to quality human resources, and (3) periodic evaluation of training programmes to ensure suitability and relevance to organisational needs. It is expected that with the implementation of these strategies, the quality of the Navy's recruitment can be improved, and the resulting personnel are better prepared to face the growing demands of the task.